Accurate genotyping of hepatitis C virus through nucleotide sequencing and identification of new HCV subtypes in China population. (September 2015) - Tong, Y.-Q.; Liu, B.; Liu, H.; Zheng, H.-Y.; Gu, J.; Liu, H.; Song, E.J.; Song, C.; Li, Y.
Abstract: Nucleotide sequencing of the phylogenetically informative region of NS5B remains the gold standard for hepatitis C virus (HCV) genotyping. Here we developed a new methodology for sequencing new NS5B regions to increase the accuracy and sensitivity of HCV genotyping and subtyping. The eight new primers were identified by scanning the full-length NS5B regions from 1127 HCV genomic sequences found in HCV databases. The ability of each pair of primers to amplify HCV subtypes was scored, and the new primers were able to amplify the NS5B region better than the previously used primers, therefore more accurately subtyping HCV strains. Sequencing the DNA amplified by the new primer pairs can specifically and correctly detect the five standard HCV subtypes (1a, 2a, 3b, 6a and 1b). We further examined patient samples and found that the new primers were able to identify HCV subtypes in clinical samples with high sensitivity. This method was able to detect all subtypes of HCV in 567 clinical samples. Importantly, three novel HCV subtypes (1b-2a, 1b-2k and 6d-6k) were identified in the samples, which have not been previous reported in China. In conclusion, sequencing the NS5B region amplified by the new NS5B primers is a more reliable method of HCV genotyping and a more sensitive diagnostic tool than sequencing using the previously described primers, and could identify new HCV subtypes. Our research is useful for clinical diagnosis, guidance of clinical treatment, management of clinical patients, and studies on the epidemiology of HCV.